Pengaruh Kebijakan Kelola Hutan Berbasis Komunitas terhadap Kesejahteraan Petani dan Konservasi Spesies Endemik di Wilayah Perbatasan Hutan Negara - Edom Bayau; Hendro Christi Suhry; Misda Alberto Senen; Fanny Soselisa (Tumbuhan : Publikasi Ilmu Sosiologi Pertanian Dan Ilmu Kehutanan, 2024)
Introduction: Land tenure conflicts and forest degradation in national forest border areas have become a complex challenge that impacts social stability and environmental sustainability. These conflicts often arise due to uncertainty in land ownership rights, leading to tensions between local communities, the government, and private companies, resulting in environmental damage such as deforestation. Community-Based Forest Management (CBFM) has emerged as a mitigation approach to address these issues by involving local communities in the sustainable management of forests. Research objective: To evaluate the impact of CBFM policies on the well-being of farmers and the conservation of endemic species in national forest border areas. Research method: A mixed-methods approach, combining household income surveys, in-depth interviews, Focus Group Discussions (FGD), and land cover analysis based on GIS. Research results: The CBFM policy has successfully increased farmers' income, particularly through forest-based business diversification, reduced illegal logging, and supported the preservation of endangered endemic species. Additionally, active community participation in this policy has increased compliance with environmental conservation efforts. This study recommends enhancing local community capacity, strengthening inter-agency coordination, and implementing stricter supervision to ensure the sustainability of the CBFM policy. The success of CBFM implementation is expected to be applied more broadly to achieve farmers' welfare and sustainable forest conservation in Indonesia.